Design reuse in the conceptual schema of CMSs: A pattern-based evaluation approach. (May 2016) - Vassiliki, Gkantouna; Sioutas, Spyros; Tsakalidis, Athanasios; Tzimas, Giannis; Viennas, Emmanouil
Abstract: This paper addresses the inspection and evaluation of design reuse in the conceptual schema of CMS-based Web applications in order to improve their design quality. We have utilized WebML as the design platform of our approach and we capture design reuse by detecting all the recurrent design structures within the hypertext schema of an application. We propose a methodology for automatically extracting the hypertext schema of an application which is then submitted to a pattern-based analysis in order to detect all the incorporated recurrent patterns implying design reuse. A pattern is a design structure consisting of a core specification, i.e., an invariant composition of WebML elements that characterizes the pattern and by a number of pattern variants which extend the core specification with all the valid modalities in which the pattern composition can start (starting variants) or terminate (termination variants). Finally, we apply a number of metrics on the identified patterns to evaluate the appropriateness of reuse which results in categorizing them as effective or poor design solutions. By applying the methodology on a web application, developers can inspect all the design structures that occur in its design probably due to design reuse and identify: (i) either effective reusable design solutions for implementing a certain behavior that can also be used as building blocks in future designs and can even form the basis for the discovery of design patterns in CMS domain, or (ii) ineffective recurrent design fragments causing design inconsistencies which imply the need for refactoring in order to improve the application׳s quality.